BENTUK PENYAJIAN TARI GALOMBANG DUO BALEH DALAM UPACARA PERKAWINAN DI DESA MARUNGGI KECAMATAN PARIAMAN SELATAN KOTA PARIAMAN - Dina Mutiatul Khairat; Darmawati Darmawati; Herlinda Mansyur (SENDRATASIK UNP, 2018)
Abstract This article aimed to describe the persentation of Galombang Dance Duo Baleh in a Marriage Ceremony in Marunggi Village, South Pariaman Subdistrict, Pariaman. This type of research was qualitative using descriptive analysis method. The main instrument was the researcher herself with assisted by some tools such as stationery and photo cameras. Techniques of data collection were in the form of library studies, observation, interviews and documentation. Data analysis techniques were collecting data, analyzing data, sorting data according to the Galombang Duo Baleh Presentation and then describing the data according to the issues discussed. The results of the study proved that the Galombang Duo Baleh Presentation was in the form of two groups in opposite directions. The elements of the presentation form consisted of: (1) Motion, which had 5 movements, namely: pambukak sambah, langkah tigo, lenong, tapuak, sambah akhir, (2) Floor design, only one form of formation, namely two straight lines in line. (3) Dancers, consisting of 6 men in groups. (4) Music, which was used by gandang tambua, tasa and sarunai (5) costumes, which were used by Galombang Duo Baleh players such as black taluak balango, black pants, sarongs made as a side. (6) The equipment used in the perfoemance of Galombang Duo Baleh was a carano containing complete sirih which was covered by fabric. (7) The place and time of the show, holding on the street exactly in front of the bride's house in the afternoon. Keywords:                 Presentation, Galombang Dance Duo Baleh, Marriage Ceremony